2013
DOI: 10.1109/tpel.2012.2209460
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel DC-Link Inverter and Control Algorithm to Overcome the PV Partial Shading

Abstract: This letter presents for the first time the application of multilevel dc-link inverter to overcome the problem of partial shading of individual photovoltaic (PV) sources which are connected in series. The "PV permutation algorithm," as a new method, is developed for the control of the inverter so as to extract the maximum power form each PV source under partial shading and to deliver all that power to the load. The algorithm is based on combination of the direct pulsewidth modulation, the sequential permutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(40 citation statements)
references
References 8 publications
(6 reference statements)
0
40
0
Order By: Relevance
“…Unlike the basic algorithm [5], the improved algorithm does not represent the PV source at the output if its offset voltage is zero, except in the case when all offset voltages are zero. The reason for introducing this exception is to initiate the control and it is also required in the case of low PWM reference signals.…”
Section: Permutation Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike the basic algorithm [5], the improved algorithm does not represent the PV source at the output if its offset voltage is zero, except in the case when all offset voltages are zero. The reason for introducing this exception is to initiate the control and it is also required in the case of low PWM reference signals.…”
Section: Permutation Algorithmmentioning
confidence: 99%
“…To compare the improved algorithm with its precursor [5], the Fast Fourier Transformation (FFT) is applied to the output waveform to find the voltage spectrum and the total harmonics distortion (THD) which is calculated for the first thousand harmonics. The waveforms were simulated for the five and seven-level DC-link converters operating in the PV system with parameters given in Table 3.…”
Section: Simulation Of the System Performancementioning
confidence: 99%
See 1 more Smart Citation
“…An initial investigation [11] has demonstrated the basic converter topology and control concept. It has been shown that the scheme allows flexible control of each PV source to make it operating at its respective MPP corresponding to its light level.…”
Section: Introductionmentioning
confidence: 99%
“…For this, a new modulation method is proposed to achieve dynamic capacitor voltage balance. In [21], a multilevel DC-link inverter is presented to overcome the problem of partial shading of individual photovoltaic sources that are connected in series. The DC bus of a full-bridge inverter is configured by several individual DC blocks, where each DC block is composed of a solar cell, a power electronic switch, and a diode.…”
mentioning
confidence: 99%